Metabolic Stroke in Biotinidase Deficiency: A Case Report - Meher, Bijay Kumar; Das, Leena; Mohanty, Anil Kumar (Asian Journal of Clinical Pediatrics and Neonatology, 2014)
An apparently normal infant born out of non-consanguineous marriage presented with abnormal movements, seizures, respiratory failure and coma at 3 months of age. MRI Brain revealed bilateral corona radiata and internal capsule acute ischemic insult with supra-tentorial early brain shrinkage. Multiple carboxylase deficiency was suspected clinically in view of erythematous skin rash, alopecia, seborrhoea and metabolic acidosis. Biotin was started and baby showed dramatic clinical improvement. Screening for inborn errors of metabolism from blood spot was positive for biotinidase deficiency and biotinidase enzyme activity in serum was low (0.17nmol/min/ml) confirming the diagnosis. The baby was treated with Biotin supplementation and on follow up at 30 months of age baby had minimal developmental delay and normal MRI of Brain.